NC Palladacycles and C, C-chelating phosphorus ylide complexes: synthesis, X-ray characterization, and comparison of the catalytic activity in the Suzuki-Miyaura reaction. Issue 5 (3rd March 2016) - Karami, Kazem; Hosseini-Kharat, Mahboubeh; Shirani-Sarmazeh, Zahra; Zahedi-Nasab, Reza; Rizzoli, Corrado; Lipkowski, Janusz
Abstract: Six secondary amine palladacycles bearing monodentate ligands (1a, 2a ), 1, 2-bis(diphenylphosphino)ethane (dppe) and 1, 3-bis(diphenylphosphino)propane (dppp) containing bridging and bidentate ligands (1b, 2b –d ), and four C, C -type phosphorus ylide complexes containing thiourea (tu) (3a ), phenyl isothiocyanate (4a ), and bridging and terminal azide groups (5 and5a ) have been synthesized. Resulting complexes have been characterized by elemental analyses, IR, 1 H-, 13 C 1 H-, and 31 P 1 H-NMR spectroscopy with single crystal X-ray structure determination of1a and2a . The Pd in1a and2a occupies the center of a slightly distorted square planar environment formed by C aryl, N amine, N pyridine, and Cl. The catalytic efficiency of complexes showed that in most cases, amine palladacycles display better catalytic activities than the phosphorus ylide Pd(II) complexes. Comparison between bidentate and bridging dppe complexes showed that dppe-bridged dimer2d has higher catalytic activity than dppe bidentate complex. Abstract :